Which Hop Tests Can Best Identify Functional Limb Asymmetry in Patients 9-12 Months After Anterior Cruciate Ligament Reconstruction Employing a Hamstrings Tendon Autograft? - Jay R Ebert; Luke Du Preez; Bonnie Furzer; Peter Edwards; Brendan Joss (International Journal of Sports Physical Therapy, 2021)
# Background Hop tests are commonly employed to evaluate functional limb symmetry after anterior cruciate ligament reconstruction (ACLR).